Online assessment for smart learning - Seladurai, Gayathri; Lang, Teresa; Jaul, Anna Theresa (Universiti Malaysia Sarawak, UNIMAS, 2003)
Web-based application becomes more significant in the software development area because of rapid growth of Internet as the largest computer in the world.